VARIATION IN AGGRESSIVENESS AND AFLP AMONG Alternaria solani ISOLATES FROM INDONESIA - Chaerani Chaerani; M. Kosim Kardin; Suhardi Suhardi; Eri Sofiari; Ria V. van Ginkel; Remmelt Groenwolt; Roeland E. Voorrips (Indonesian Journal of Agricultural Science, 2017)
Alternaria solani is a necrotroph fungus that causes three-phased diseases in tomato. Management of the pathogen by using resistant cultivars requires knowledge on the aggressiveness and genetic diversity of the fungus. The aims of this study were to isolate A. solani from major tomato and potato producing areas in Indonesia and to study their aggressiveness and genetic variability. Twenty two A. solani isolates were recovered from early blighted tomato and potato in Central and West Java.  A. alternata was also isolated from tomato leaves in West Java and North Sumatra, indicating that early blight in Indonesia may be caused by more than one Alternaria species. Resistance tests of four tomato genotypes to selected A. solani isolates revealed that local isolates were more aggressive in inciting early blight and stem lesion than an imported isolate from USA. This implies that introduced breeding materials must be tested to local isolates to obtain effective resistance genes. Cluster analysis based on amplified fragment length polymorphism (AFLP) obtained from EcoRI+AG and MseI+C primer amplification separated 28 local and Taiwan isolates from the US isolate, which was coincided with aggressiveness separation between the local isolates and the US isolate. Three clusters of AFLP genotypes which did not associate with geographic origin were observed among tropical isolates. The low genetic diversity among the Indonesian isolates suggests clonal population structure with wide distribution. Successful local tomato breeding requires the availability of local A. solani collection with well-characterized aggressiveness level and molecular diversity to obtain effective resistance genes.